ANALYZING THE SERVICE QUALITY OF SILOAM HOSPITAL MANADO USING IMPORTANCE AND PERFORMANCE ANALYSIS (IPA) - Tambajong, Christy Emmanuela; Saerang, David P.E. (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2016)
Abstract: Hospital plays an important role in preventing disease and providing rehabilitation service to people. In current rapidly growing consumer-oriented health industry, quality has become the integral part. To meet the demand for world-class medical services by a growing Indonesian middle class as well as the demand from the introduction of the national health-care plan, private hospital is rapidly increasing the numbers of hospitals and broadening the service it offers. This research aims to analyze the service quality of Siloam Hospital Manado. The type of this research is a quantitative descriptive research. The Imporance Performance Analysis (IPA) was used in this research. The sample of this research is 100 respondents who already experience the service quality of Siloam Hospital Manado. The sample was taken by Purposive Sampling. This research suggests that Siloam Hospital needs to improve their performance and giving the best services for consumer. By doing so, it is hoped that their consumers will be satisfied and will be their loyal customers. Â  Keywords: Service Quality, Importance Performance Analysis, Health-Care Industry, Hospital